PENGARUH KOMBINASI PUPUK KANDANG DENGANUREA TERHADAP PERTUMBUHAN SAWI (Brassica juncea L.) - Ida Yuliani; Septiana Dwi Utami; Ismail Efendi (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2018)
This study aims to determine the effect of combination of manure with urea on mustard greens. This type of research is true experiment. The experiment was conducted in experimental garden located in Pejeruk Bangket neighborhood of Pejeruk Village, Ampenan District, Mataram City. The research was using Completely Randomized Design (RAL) with 4 treatment of 6 replications with combination of manure with different urea on mustard plant P0 (Control), P1 (100% manure), P2 (50% manure + 50% urea fertilizer) P3 (100% urea fertilizer). The data of the research were analyzed using Analysis of Variance and continued by Duncan test if there was effect of cow manure komninasi treatment with urea to growth of mustard greens. The results showed that the combination of manure with urea on the growth of the mustard greens had a significant effect on plant height and wet weight, while the leaf length and leaf width did not significantly affect. The effect of fertilizer combination shows different results on each parameter. In the highest plant growth parameter height at P2; Leaf length at P1; leaf width at P1; and wet weight on P2.